Embryonic perfect repair inspired electrospun nanofibers dressing with temperature-sensitive and antibacterial properties for wound healing - Qi, Qinbing; Li, Rongkai; Wang, Chunhua; Hou, Guige; Li, Chengbo (Frontiers in Microbiology, 2023)
The development of highly effective wound dressings is crucial for successful clinical applications. Achieving wound closure, preventing infection, and minimizing scarring are key objectives in wound healing. Drawing inspiration from the regenerative mechanisms observed in embryonic tissue repair, we designed a series of wound-contractible dressings with exceptional antibacterial properties. This was achieved by encapsulating quaternized silicone (QP12) and poly(Nisopropylacrylamide-co-N-hydroxymethylacrylamide-co-octadecyl acrylate) (PNNS) within electrospun nanofibers of poly(ε-caprolactone) (PCL). The resulting nanofibrous dressings demonstrated remarkable thermothermo-responsive self-contraction and tissue adhesion capabilities, enabling secure adherence to the skin and active wound closure. Notably, these nanofibers exhibited potent antibacterial activity against both Gram-positive and Gram-negative bacteria. Furthermore, they possessed desirable properties such as hydrophilicity, biocompatibility and mechanical properties resembling human skin. A full-thickness skin defect model evaluation revealed that these temperaturesensitive nanofibers expedited wound closure, enhanced wound healing, and suppressed scar formation. This result was evidenced by reduced infiltration of inflammatory cells, well-organized collagen arrangement, and improved vascularization. In summary, we propose that these wound-contractible nanofibers, with their antibacterial and anti-scarring properties, hold great promise as an advanced solution for skin wound repair.